2014
DOI: 10.1002/2014ja020205
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection, buoyancy, and flapping motions in magnetotail explosions

Abstract: A key process in the interaction of magnetospheres with the solar wind is the explosive release of energy stored in the magnetotail. Based on observational evidence, magnetic reconnection is widely believed to be responsible. However, the very possibility of spontaneous reconnection in collisionless magnetotail plasmas has been questioned in kinetic theory for more than three decades. In addition, in situ observations by multispacecraft missions (e.g., THEMIS) reveal the development of buoyancy and flapping mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
111
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(127 citation statements)
references
References 106 publications
16
111
0
Order By: Relevance
“…Tailward of the DF a new X line forms because of the flux starvation effect (e.g., Bessho & Bhattacharjee, 2014;Pritchett, 2015;Sitnov et al, 2013) as is seen from Figure 1a showing the distribution of the equatorial magnetic field B z (x, z = 0) at 0i t = 32. They were identified earlier (Sitnov et al, 2014) as signatures of the long-wavelength (∼ 2 √ 0i 0e ) modification (Daughton, 2003) of the lower-hybrid drift instability (LHDI) of thin CSs with zero B z component (Huba et al, 1977), which is also similar in case of nonzero B z to the kinetic ballooning/interchange instability (Pritchett & Coroniti, 2010). It reveals in particular the formation of the EDR as identified by the enhancement of j ⋅ E ′ near the X line .…”
Section: Simulation Setup and Resultsmentioning
confidence: 88%
“…Tailward of the DF a new X line forms because of the flux starvation effect (e.g., Bessho & Bhattacharjee, 2014;Pritchett, 2015;Sitnov et al, 2013) as is seen from Figure 1a showing the distribution of the equatorial magnetic field B z (x, z = 0) at 0i t = 32. They were identified earlier (Sitnov et al, 2014) as signatures of the long-wavelength (∼ 2 √ 0i 0e ) modification (Daughton, 2003) of the lower-hybrid drift instability (LHDI) of thin CSs with zero B z component (Huba et al, 1977), which is also similar in case of nonzero B z to the kinetic ballooning/interchange instability (Pritchett & Coroniti, 2010). It reveals in particular the formation of the EDR as identified by the enhancement of j ⋅ E ′ near the X line .…”
Section: Simulation Setup and Resultsmentioning
confidence: 88%
“…Several theoretical models predict the substantial variations in B z with x in oscillating CSs Pritchett and Coroniti, 2010;Sitnov et al, 2014). The large distances between Cluster spacecraft allow us to investigate the homogeneity of the flapping wave within spatial scale around 10 4 km (i.e.…”
Section: Statistics Of Cs Parametersmentioning
confidence: 99%
“…This is clear from equations and showing that the stabilizing term under the integral (the last one) is inversely proportional to the equilibrium flux tube volume; i.e., the flux tube has to be sufficiently long to reduce the stabilizing term and allow an instability (this is equivalent to saying that Cd1). The previous kinetic simulations [ Sitnov et al ., , ; Bessho and Bhattacharjee , ] effectively resolved this problem by using simulations with open boundaries. While computational constraints in MHD simulations are not as stringent, expanding the simulation box is still challenging.…”
Section: Energy Principle Considerationsmentioning
confidence: 99%
“…Since the analysis of Sitnov and Schindler [] showed that the kinetic stabilization parameter can be reduced in equilibria with a magnetic flux accumulation leading to a potential for instability, it is plausible to contemplate that it may not be sufficiently stabilizing in ideal MHD either. In addition, kinetic simulations [ Sitnov and Swisdak , ; Sitnov et al ., , ; Bessho and Bhattacharjee , ] reveal interesting plasma dynamics, e.g., the formation of a DF, prior to a change in topology (magnetic reconnection per se). Although those dynamics are not necessarily ideal, the fact that they take place before reconnection motivates us to investigate the same equilibrium configurations in the MHD approximation.…”
Section: Introductionmentioning
confidence: 99%